Hyponatremia in severe malaria: evidence for an appropriate anti-diuretic hormone response to hypovolemia. - Hanson, J; Hossain, A; Charunwatthana, P; Hassan, M; Davis, T; Lam, S; Chubb, SA; Maude, R; Yunus, E; Haque, G; White, N; Day, N; et al. (2009)
Although hyponatremia occurs in most patients with severe malaria, its pathogenesis, prognostic significance, and optimal management have not been established. Clinical and biochemical data were prospectively collected from 171 consecutive Bangladeshi adults with severe malaria. On admission, 57% of patients were hyponatremic. Plasma sodium and Glasgow Coma Score were inversely related (r(s) = -0.36, P < 0.0001). Plasma antidiuretic hormone concentrations were similar in hyponatremic and normonatremic patients (median, range: 6.1, 2.3-85.3 versus 32.7, 3.0-56.4 pmol/L; P = 0.19). Mortality was lower in hyponatremic than normonatremic patients (31.6% versus 51.4%; odds ratio [95% confidence interval]: 0.44 [0.23-0.82]; P = 0.01 by univariate analysis). Plasma sodium normalized with crystalloid rehydration from (median, range) 127 (123-140) mmol/L on admission to 136 (128-149) mmol/L at 24 hours (P = 0.01). Hyponatremia in adults with severe malaria is common and associated with preserved consciousness and decreased mortality. It likely reflects continued oral hypotonic fluid intake in the setting of hypovolemia and requires no therapy beyond rehydration.